Program Sosialisasi di Lembaga Pendidikan Taman Kanak-Kanak Dharmawanita Penanggungan - Muhammad Risydan Al Amin; Widyasari Widyasari (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
Village development is a form of community service carried out by students by immersing themselves directly in the community environment so that when students study in the community and know the problems faced in that environment, the PKKM Village Development Program is expected to be a learning medium for students and the problems they face. The community can be helped and get solutions from the knowledge applied by students. PKKM Bina Desa Tawas 2023, which is located in Penanggungan Village, Trawas District, Mojokerto Regency, has been running a work program for 3 months from 21 August - 24 November 2023. One of the work programs I am working on is a program at the Dharmawanita Penanggungan Kindergarten educational institution, Problem What happened at the Dharma Wanita Penanggungan Kindergarten was the change in the mural on the classroom wall, where the previous mural had been damaged, peeling and there was a lot of graffiti from the kindergarten students, so the kindergarten team and I repaired and renovated the classroom wall. Therefore, the mural program on Kindergarten classroom walls can help Kindergarten students become enthusiastic about learning and we also provide empty walls that are not filled with murals to enable Kindergarten students to express themselves on the walls. The mural program at the Kindergarten has been completed on time and is being done as well as possible. Keywords: PKKM, Village Development, Penanggungan Village, Kindergarten, Mural.